Preventive Behaviors During the COVID-19 Pandemic: Associations With Perceived Behavioral Control, Attitudes, and Subjective Norm - Aschwanden, Damaris; Strickhouser, Jason E.; Sesker, Amanda A.; Lee, Ji Hyun; Luchetti, Martina; Terracciano, Antonio; Sutin, Angelina R. (Frontiers in Public Health, 2021)
Background: The coronavirus disease 2019 (COVID-19) is a highly contagious and potentially fatal infectious disease that has swept the globe. To reduce the spread, it is important to engage in preventive behaviors recommended by health authorities, such as washing your hands, wearing a face mask, and social distancing. Aim: In the present study, we draw from the Theory of Planned Behavior (TPB) to examine the associations between perceived behavioral control, attitudes, and subjective norm and whether people engage in eight different preventive behaviors. Method: For each of the preventive behaviors (washing hands; using hand sanitizer; not touching your face; social distancing; wearing a face mask; disinfecting surfaces; coughing in your elbow; staying home if sick), we conducted separate logistic regressions predicting whether the participants (N = 2,256; age range = 18-98 years) reported engaging in the behavior from their perceived behavioral control, attitudes, and subjective norm. Results: We found that perceived behavioral control, attitudes, and subjective norm had independent significant associations with each preventive behavior. Moderation analyses revealed that for most behaviors the associations with perceived behavioral control were stronger for older adults than for younger adults. Limitation: The present study was cross-sectional; future longitudinal studies and interventions are needed to disentangle directionality. Conclusion: Our findings suggest several ways to increase adherence to health behaviors that reduce the spread of coronavirus and other infectious diseases.